Candlelight for Rebecca - Greene, Jacqueline Dembar (American Girl Pub., 2009)
While Rebecca Rubin helps her building's ailing superintendent take care of his homing pigeons, she puzzles over what to do with the Christmas centerpiece her teacher insisted she make but which has no place in her Jewish home.